2020
DOI: 10.1590/1807-3107bor-2020.vol34.0049
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic perceptions and social judgments about different enamel opacities

Abstract: Marcela Baraúna MAGNO (a) Aline Borburema NEVES (a) Raildo da Silva COQUEIRO (b) Marcelo de Castro COSTA (a) Lucianne Cople MAIA (a) Matheus Melo PITHON (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…This supports the theory for which the general population label a whiter color as more aesthetic. This conclusion is supported by the literature, in a work by Samorodnitzky-Naveh et al, [29][30][31] laypeople were found to assess their teeth darker than clinicians and they asked to have a bleaching treatment in the future.…”
Section: Discussionsupporting
confidence: 58%
“…This supports the theory for which the general population label a whiter color as more aesthetic. This conclusion is supported by the literature, in a work by Samorodnitzky-Naveh et al, [29][30][31] laypeople were found to assess their teeth darker than clinicians and they asked to have a bleaching treatment in the future.…”
Section: Discussionsupporting
confidence: 58%
“…Concern with the color of teeth is related to the need to make a good first impression on other people 28 since people judge physical appearance, including weight, height, and dentofacial aesthetics 29 . This aesthetic factor concerns oral health, especially among adolescents, who have high aesthetic demand, as previously mentioned, and who are undergoing physiological and physical changes 30 . Additionally, more important than the pain and loss of function with tooth loss for adolescents is the shame of not having a tooth 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Understanding the patient and his needs, as well as helping him to understand them, is the first step in order to offer appropriate and individualized aesthetic treatments (Aldeeri et al, 2020;Silva et al, 2020). Research, Society andDevelopment, v. 11, n. 3, e21111326326, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i3.26326 6…”
Section: Discussionmentioning
confidence: 99%